UROGENITAL INFECTION IN THE LIGHT OF THE RISING SUN - E. V. Kulchavenya (Вестник урологии)
The report author shares his impressions of the Congress of the International Society of Chemotherapy infections and cancer, which took place from 5th to 8th June 2013 in Yokohama, Japan.